A large family with hereditary spastic paraparesis due to a frame shift mutation of the spastin (SPG4) gene: association with multiple sclerosis in two affected siblings and epilepsy in other affected family members. Issue 6 (1st December 2001) - Mead, S H; Proukakis, C; Wood, N; Crosby, A H; Plant, G T; Warner, T T
Abstract : Hereditary spastic paraparesis (HSP) is a clinically and genetically heterogeneous neurodegenerative disorder characterised by progressive lower limb spasticity and weakness. Some forms have been associated with white matter lesions and complex phenotypes. This study was prompted by the diagnosis of multiple sclerosis (MS) in two sisters from a large pedigree with hereditary spastic paraparesis. Twelve affected members of the extended family were examined (MRI and EEG were carried out and evoked potentials measured in five), and historical information was obtained from six affected deceased persons. The inherited disease phenotype was confirmed as autosomal dominant hereditary spastic paraparesis associated with epilepsy in four affected persons. None of the extended family had evidence of MS. Genetic analysis of the family has shown linkage to chromosome 2p and sequencing of the spastin gene has identified a 1406delT frameshift mutation in exon 10. This kindred demonstrates the clinical heterogeneity of HSP associated with spastin mutations. The possible relevance of the concurrence of HSP and MS in the sib pair is discussed.